Novel applications of Morita-Baylis-Hillman methodology in organic synthesis - Mciteka, Lulama Patrick (Rhodes University, Faculty of Science, Department of Chemistry, 2013)
The overall approach in the present investigation has been to explore applications of the Morita-Baylis-Hillman (MBH) reaction in asymmetric synthesis and in the continuation of systems with medicinal potential. To this end, a series of varied camphor-derived acrylate esters was prepared to serve as chiral substrates in asymmetric Morita-Baylis- Hillman reactions. Reduction of N-substituted camphor-10-sulfonamides afforded the 3- exo-hydroxy derivatives as the major products. Acylation of the corresponding sodium alkoxides gave the desired 3-exo-acrylate esters, isolation of which was complicated by concomitant formation of hydrochlorinated and diastereomeric competition products. Bulky camphorsulfonamides containing alkyl, dialkyl, aromatic and adamantyl groups were selected as N-substituents with the view of achieving stereoselective outcome in subsequent MBH reactions. The synthesis of novel camphor-derived Morita-Baylis-Hillman adducts using various pyridine-carboxaldehydes proceeded with exceptionally high yields with diastereoselectivities ranging from 7-33 % d.e. Both 1D and 2D NMR and HRMS techniques were employed to confirm the structures and an extensive study of the electropositive fragmentation patterns of a number of camphor-derived chiral acrylate esters was conducted. Attention has also been given to the application of MBH methodology in the construction of heterocyclic 'cinnamate-like' AZT conjugates which were designed to serve as dualaction HIV-1 integrase-reverse transcriptase (IN-RT) inhibitors. A number of pyridine carboxaldehyde-derived MBH adducts were synthesized using methyl, ethyl and t-butyl acrylates in the presence of 3-hydroxyquinuclidine (3-HQ) as catalyst. The yields for these reactions were excellent. The resulting MBH adducts were acetylated and subjected to aza-Michael addition using propargylamine. The resulting alkylamino compounds were then used in 'Click reactions' to form the targeted AZT-conjugates in moderate to excellent yield. In silico docking of computer modelled AZT-conjugates into the HIV-1 integrase and reverse transcriptase enzyme-active sites and potential hydrogen-bonding interaction with active-site amino acid residues were identified. The electrospray MS fragmentations of the AZT and the novel AZT-conjugates were also investigated and common fragmentation pathways were identified.
Keywords: Organic compounds -- Synthesis -- Research; Asymmetric synthesis; Asymmetry (Chemistry); Chemical reactions -- Research; Camphor -- Research; AZT (Drug) -- Research; Chemical inhibitors -- Research; Chemistry -- Methodology